A Review of the Diagnosis and Treatment of Limbal Stem Cell Deficiency - Kate, Anahita; Basu, Sayan (Frontiers in Medicine, 2022)
Limbal stem cell deficiency (LSCD) can cause significant corneal vascularization and scarring and often results in serious visual morbidity. An early and accurate diagnosis can help prevent the same with a timely and appropriate intervention. This review aims to provide an understanding of the different diagnostic tools and presents an algorithmic approach to the management based on a comprehensive clinical examination. Although the diagnosis of LSCD usually relies on the clinical findings, they can be subjective and non-specific. In such cases, using an investigative modality offers an objective method of confirming the diagnosis. Several diagnostic tools have been described in literature, each having its own advantages and limitations. Impression cytology and in vivo confocal microscopy (IVCM) aid in the diagnosis of LSCD by detecting the presence of goblet cells. With immunohistochemistry, impression cytology can help in confirming the corneal or conjunctival source of epithelium. Both IVCM and anterior segment optical coherence tomography can help supplement the diagnosis of LSCD by characterizing the corneal and limbal epithelial changes. Once the diagnosis is established, one of various surgical techniques can be adopted for the treatment of LSCD. These surgeries aim to provide a new source of corneal epithelial stem cells and help in restoring the stability of the ocular surface. The choice of procedure depends on several factors including the involvement of the ocular adnexa, presence of systemic co-morbidities, status of the fellow eye and the comfort level of the surgeon. In LSCD with wet ocular surfaces, autologous and allogeneic limbal stem cell transplantation is preferred in unilateral and bilateral cases, respectively. Another approach in bilateral LSCD with wet ocular surfaces is the use of an autologous stem cell source of a different epithelial lineage, like oral or nasal mucosa. In eyes with bilateral LSCD with significant adnexal issues, a keratoprosthesis is the only viable option. This review provides an overview on the diagnosis and treatment of LSCD, which will help the clinician choose the best option amongst all the therapeutic modalities currently available and gives a clinical perspective on customizing the treatment for each individual case.